Constitution makers on constitution making new cases - Ginsburg, Tom 1967-; Bisarya, Sumit ca. 20./21. Jh (Comparative constitutional law and policy, 2022)
Constitution-making is a major event in the life of a country, with constitutions often acting as a catalyst for social and political transformation. But what determines the visions, aspirations and compromises that go into a written constitution? In this unique volume, constitution makers from countries around the world come together to offer their insights. Using a collection of case studies from countries with recently written constitutions, Constitution Makers on Constitution Making provides a common framework to explain how constitutions are created. Scholars and practitioners very close to the process illuminate critical insights into how participants see constitutional options, how deadlocks are broken, and how changes are achieved. This vital volume also draws lessons concerning the role of courts in policing the process, on international involvement, and on public participation